Influence of integrated nutrient combinations on relative storability of fennel (Foeniculum vulgare) seed - Kumar, Vikash; Malik, T P; Mor, V S; Choudhary, Desh Raj; Vikram, Vikram (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during rabi 2016–17 and 2017–18 at Research Farm of CCS Haryana Agricultural University, Hisar. It comprised of sixteen treatment levels of fertilizer in randomized block design with three replications. After proper drying, cleaning and attaining the optimum moisture content the seeds were collected and the completely randomized design (CRD) was followed to conduct laboratory testing for the seed relative storability parameters in the seed testing laboratory, CCS Haryana Agricultural University, Hisar. After accelerated ageing for 24, 48, 72, 96 and 120 h the seed received from the treatment T9: 100% RDN through vermicompost + Azotobacter + PSB showed highest standard germination (87.83, 77.34, 69.39, 52.34 and 27.17%), seedling length (20.95, 18.93, 16.15, 14.95 and 12.50 cm), seedling dry weight (3.77, 3.44, 2.84, 2.21 and 1.87 g) and seed vigour index-I (1837, 1474, 1119, 780 and 339) and seed vigour index-II (330.7, 265.7, 196.9, 115.2 and 50.6) in treatment T9: 100% RDN through vermicompost + Azotobacter + PSB. The least value observed in treatment T16: control. The lowest value of electrical conductivity at 24, 48, 72, 96 and 120 hours (144.8, 233.0, 353.1, 497.7, 697.78 μS/cm/g) was observed in treatment T9: 100% RDN through vermicompost + Azotobacter + PSB the same treatments while the highest value was observed in (T16) control (190.1, 302.9, 434.1, 602.2, 841.8 μS/cm/g) on pooled mean basis.